2022
DOI: 10.1038/s41598-022-08563-9
|View full text |Cite
|
Sign up to set email alerts
|

The steroid hormone ecdysone regulates growth rate in response to oxygen availability

Abstract: In almost all animals, physiologically low oxygen (hypoxia) during development slows growth and reduces adult body size. The developmental mechanisms that determine growth under hypoxic conditions are, however, poorly understood. Here we show that the growth and body size response to moderate hypoxia (10% O2) in Drosophila melanogaster is systemically regulated via the steroid hormone ecdysone. Hypoxia increases level of circulating ecdysone and inhibition of ecdysone synthesis ameliorates the negative effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…Our results are similar to a previous report that examined the effects of moderate hypoxia (10% oxygen) and showed that hypoxia exposure delayed the maturation-inducing ecdysone pulse at the end of the larval period [ 46 ]. Interestingly this study also found that hypoxia exposure early in the third instar led to elevated hemolymph ecdysone titers and a subsequent study reported that this elevated ecdysone signaling led to reduced body growth by inducing expression of ImpL2, a negative regulator of systemic insulin signaling [ 47 ]. These results suggest that hypoxia exposure may have different effects on ecdysone depending on the stage of larval development.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Our results are similar to a previous report that examined the effects of moderate hypoxia (10% oxygen) and showed that hypoxia exposure delayed the maturation-inducing ecdysone pulse at the end of the larval period [ 46 ]. Interestingly this study also found that hypoxia exposure early in the third instar led to elevated hemolymph ecdysone titers and a subsequent study reported that this elevated ecdysone signaling led to reduced body growth by inducing expression of ImpL2, a negative regulator of systemic insulin signaling [ 47 ]. These results suggest that hypoxia exposure may have different effects on ecdysone depending on the stage of larval development.…”
Section: Discussionmentioning
confidence: 93%
“…The delayed attainment of CW caused by hypoxia exposure in early larval development is most likely due to a similar lowering of systemic insulin/TOR. For example, hypoxia has been shown to promote HIF-1-alpha-independent inhibition of TOR signaling [ 49 , 50 ], suppress systemic insulin signaling by reducing insulin secretion from the brain [ 48 , 49 ], and upregulate expression of the insulin antagonist, ImpL2 [ 47 ]. These suppressive effects of hypoxia on insulin/TOR signaling would also persist post CW to reduce late larval growth and hence lead to smaller body size compared to normoxic larvae.…”
Section: Discussionmentioning
confidence: 99%
“…CW is determined, in large part, by an animal's growth rate, which in Drosophila larvae is controlled by the conserved insulin and TOR kinase signaling pathways (Malita and Rewitz, 2021). Given that hypoxia exposure can suppress larval growth by inhibiting these pathways (Barretto et al, 2020;Kapali et al, 2022;Lee et al, 2019;Texada et al, 2019;Wong et al, 2014), it is possible that the delay in maturation merely reflects a hypoxia-induced delay in attainment of CW. To address this, we raised larvae from hatching in either normoxia or hypoxia and then at defined times in development we switched them to starvation conditions and monitored their subsequent development in normoxia.…”
Section: Resultsmentioning
confidence: 99%
“…The 10 delayed attainment of CW caused by hypoxia exposure in early larval development is most likely due to a similar lowering of systemic insulin/TOR. For example, hypoxia has been shown to promote HIF-1-alpha-independent inhibition of TOR signaling (Lee et al, 2019;Texada et al, 2019), suppress systemic insulin signaling by reducing insulin secretion from the brain (Texada et al, 2019;Wong et al, 2014), and upregulate expression of the insulin antagonist, ImpL2 (Kapali et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation